Sintering effects on mechanical properties of hydroxyapatite-titanium dioxide (HA-TiO2) composites - (:unkn) unknown (TRANS TECH PUBLICATIONS LTD, 2006)
Composites of bovine bone derived HA with 5 wt% and 10 wt% of TiO2 were sintered at different temperatures. Their characterization comprised measurements of density, microhardness, and compression strength together with SEM observations and X-ray diffraction analysis. Better densification behaviour was achieved at higher sintering temperatures. The highest microhardness value was measured in the samples sintered at 1300 degrees C. The best compressive strengths of the samples containing 5% and 10% TiO2 were obtained after sintering at 1300 degrees C and 1200 degrees C, respectively.
Keywords: hydroxyapatite; titanium oxide; sintering; mechanical properties